EXPLORING THE IMPACT OF SHARIA SUPERVISORY BOARD CHARACTERISTICS ON ENVIRONMENTAL DISCLOSURE: A GLOBAL STUDY OF ISLAMIC BANKS - Abdurrahman, Zahron; Wicaksono, Aditya Pandu (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2025)
This research assesses the extent to which Sharia Supervisory Board (SSB) traits impact the worldwide phenomenon of environmental disclosures of Islamic Banks. We used Multivariate Regression Analysis to assess the environmental disclosures of 33 Islamic Banks in the world using the GRI 300 standards obtained from the Refinitiv Database, while the SSB traits of Shariah Qualification, Financial Expertise, Gender and Nationality Diversity, Board Size, and the Annual Reports of the Banks were manually collected as SSB were visions of Mufti Shariah. The research employed Panel Data Regression using the Fixed Effects Estimator to control for unobserved heterogeneity around the Banks and to ensure the reliability of the findings. The results showed that Gender and National Diversity had a positive effect on Mukahara Shariah, meaning that more Diversity in Religion and Nationality of the Board Members led to more disclosure. In contrast, Shariah Qualification had a negative effect, while financial expertise and Board Size had no effect.  The research results demonstrate the importance of SSB to advance the Disclosure of Sustainability Reporting Construction to the elders, that SSBs must give More Priority to diversity over traditional religious qualifications. The research results have effectively empowered the Regulators of Islamic Financial Institutions to complement the SSBs to include the Responsible Sharia Governance of Islamic Banking Systems for Compliance with the Global Sustainability Standards.